Diagnostic relevance of IgE sensitization profiles to eight recombinant Phleum pratense molecules. Issue 3 (14th December 2017) - Cipriani, F.; Mastrorilli, C.; Tripodi, S.; Ricci, G.; Perna, S.; Panetta, V.; Asero, R.; Dondi, A.; Bianchi, A.; Maiello, N.; Miraglia del Giudice, M.; Frediani, T.; et al.
Abstract: Background: Grass pollen‐related seasonal allergic rhinoconjunctivitis (SARg) is clinically heterogeneous in severity, comorbidities, and response to treatment. The component‐resolved diagnostics disclosed also a high heterogeneity at molecular level. Our study aimed at analyzing the characteristics of the IgE sensitization to Phleum pratense molecules and investigating the diagnostic relevance of such molecules in childhood. Methods: We examined 1120 children (age 4‐18 years) with SARg. Standardized questionnaires on atopy were acquired through informatics platform (AllergyCARD™). Skin prick tests were performed with pollen extracts. Serum IgE to airborne allergens and eight P. pratense molecules (rPhl p 1, rPhl p 2, rPhl p 4, rPhl p 5b, rPhl p 6, rPhl p 7, rPhl p 11, rPhl p 12) were tested by ImmunoCAP FEIA. Results: The analysis of IgE responses against eight P. pratense molecules showed 87 profiles. According to the number of molecules recognized by IgE, the more complex profiles were characterized by higher serum total IgE, higher grass‐specific serum IgE, and higher number and degree of sensitization to pollens. The most frequent IgE sensitization profile was the monomolecular Phl p 1. Sensitization to Phl p 7 was a reliable biomarker of asthma, whereas Phl p 12 of oral allergy syndrome. Sensitization to Phl p 7 was associated with a higher severity of SARg, and complex profiles were associated with longer disease duration. Conclusions: In a large pediatric population, the complexity of IgE sensitization profiles against P. pratense molecules is related to high atopic features although useless for predicting the clinical severity. The detection of serum IgE to Phl p 1, Phl p 7, and Phl p 12 can be used as clinical biomarkers of SARg and comorbidities. Further studies in different areas are required to test the impact of different IgE molecular profiles on AIT response.